Matching Dendrochronological Dates with the Southern Hemisphere 14C Bomb Curve to Confirm Annual Tree Rings in Pseudolmedia rigida from Bolivia. Issue 1 (2015) - Andreu-Hayles, Laia; Santos, Guaciara M; Herrera-Ramírez, David A; Martin-Fernández, Javier; Ruiz-Carrascal, Daniel; Boza-Espinoza, Tatiana E; Fuentes, Alfredo F; J⊘rgensen, Peter M
Abstract : This study used high-precision radiocarbon bomb-pulse dating of selected wood rings to provide an independent validation of the tree growth periodicity of Pseudolmedia rigida (Klotzsch & H. Karst) Cuatrec. from the Moraceae family, collected in the Madidi National Park in Bolivia. 14 C content was measured by accelerator mass spectrometry (AMS) in 10 samples from a single tree covering over 70 yr from 1939 to 2011. These preliminary calendar dates were determined by dendrochronological techniques and were also used to select the samples for 14 C AMS. In order to validate these preliminary dates using the established Southern Hemisphere (SH) 14 C atmospheric concentration data set, the targeted rings were selected to be formed during periods before and after the 14 C bomb spike nuclear tests (i.e. 1950s–1960s). The excellent agreement of the dendrochronological dates and the 14 C signatures in tree rings associated with the same dates provided by the bomb-pulse 14 C atmospheric values for the SH (SHCal zone 1–2) confirms the annual periodicity of the observed growth layers, and thus the high potential of this species for tree-ring analysis. The lack of discrepancies between both data sets also suggests that there are no significant latitudinal differences between the 14 C SHCal zone 1–2 curve and the 14 C values obtained from the selected tree rings at this geographic location (14°33′S, 68°49′W) in South America. The annual resolution of P. rigida tree rings opens the possibility of broader applications of dendrochronological analysis for ecological and paleoclimatic studies in the Bolivian tropics, as well as the possibility of using wood samples from some tree species from this region to improve the quality of the bomb-pulse 14 C SHCal curve at this latitude.